Estimación de sexo mediante medidas radiográficas mandibulares en individuos de 6 a 23 años. Estudio exploratorio. (2021)
The aim of this study is to explore the measurements of the condylar angle, the angle of the mandibular notch and the relationship between mandibular area and condylar-coronoid area, as estimation factors of sex, in a sample of panoramic radiographs.